Effectiveness of Field Work Practices in Increasing Therapeutic Communication Knowledge - Agustin, Amarlian Bilqisthi; Triyono, Mochamad Bruri; Wagiran, Wagiran; Santosa, Budi (Universitas Ahmad Dahlan, 2025)
Therapeutic communication is basic communication that a nursing assistant must have. The aim of this research is to determine the effectiveness of field work practice in increasing vocational high school students' knowledge of therapeutic communication. The population of this study were students in class The sampling technique was purposive sampling technique, as many as 27 students. This type of research uses a quasi-experimental design with a pretest and posttest group design. The results of the Paired Samples Test obtained a Sig (2-tailed) value of 0.015 < 0.050, indicating that there is an average difference between the pretest and posttest variables. This means that there is an influence of field work practice on students' therapeutic communication knowledge. Meanwhile, based on the One Sample Test, a Sig (2-tailed) value of 0.000 <0.050 was obtained, indicating that the average value of therapeutic communication knowledge after field work practice was not the same as 75. The conclusion is that the implementation of field work practices is not effective in increasing the therapeutic communication knowledge of students at SMK Muhammadiyah Lumajang for the 2023/2024 academic year.